The k-j-j' vector correlation in inelastic and reactive scattering. - Brouard, M; Chadwick, H; Eyles, C; Aoiz, F; Kłos, J (2011)
Quasi-classical trajectory (QCT) methods are presented which allow characterization of the angular momentum depolarization of the products of inelastic and reactive scattering. The particular emphasis of the theory is on three-vector correlations, and on the connection with the two-vector correlation between the initial and final angular momenta, j and j', which is amenable to experimental measurement. The formal classical theory is presented, and computational results for NO(A) + He are used to illustrate the type of mechanistic information provided by analysis of the two- and three-vector correlations. The classical j-j' two-vector correlation results are compared with quantum mechanical calculations, and are shown to be in good agreement. The data for NO(A) + He support previous conclusions [M. Brouard, H. Chadwick, Y.-P. Chang, R. Cireasa, C. J. Eyles, A. O. L. Via, N. Screen, F. J. Aoiz, and J. Kłos, J. Chem. Phys. 131, 104307 (2009)] that this system is only weakly depolarizing. Furthermore, it is shown that the projection of j along the kinematic apse is nearly conserved for this system under thermal collision energy conditions.